2008
DOI: 10.1002/dvdy.21792
|View full text |Cite
|
Sign up to set email alerts
|

The acyltransferase gene bus‐1 exhibits conserved and specific expression in nematode rectal cells and reveals pathogen‐induced cell swelling

Abstract: Susceptibility to the rectal pathogen Microbacterium nematophilum provides a means of examining hindgut differentiation in C. elegans. Mutants of bus-1 are resistant to infection with this pathogen. We show here that bus-1 encodes a predicted acyltransferase expressed in rectal epithelial cells (K, F, and U), suggesting its involvement in regional surface modification. bus-1 reporter genes were used to show spatial regulation by hindgut developmental control genes: egl-38, mab-9, and mab-23. A bus-1::GFP repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Activation of RHO-1* caused changes in cell morphology; cells appeared larger and were no longer organised around the rectal opening instead spreading towards the dorsal side of the animal (Figure 4 F, G, J and K). These changes were also observed in the rectal epithelial cells of wild-type animals infected with Microbacterium nematophilum (Figure 4F–I) [51]. Thus, RHO-1* acts cell-autonomously to alter rectal epithelial cell morphology in a manner similar to the innate immune response to pathogens.…”
Section: Resultsmentioning
confidence: 62%
“…Activation of RHO-1* caused changes in cell morphology; cells appeared larger and were no longer organised around the rectal opening instead spreading towards the dorsal side of the animal (Figure 4 F, G, J and K). These changes were also observed in the rectal epithelial cells of wild-type animals infected with Microbacterium nematophilum (Figure 4F–I) [51]. Thus, RHO-1* acts cell-autonomously to alter rectal epithelial cell morphology in a manner similar to the innate immune response to pathogens.…”
Section: Resultsmentioning
confidence: 62%
“…For deformable, hydrophilic surfaces like those encountered on top of an agar gel, which is the usual place for examining C. elegans in a laboratory environment, it is not obvious how traction is exerted. As already noted in characterizing bus-8, bus-17, and bus-18 mutants ( Yook and Hodgkin 2007;Gravato-Nobre and Hodgkin 2008;Partridge et al 2008), several of the surfaceabnormal mutants identified by Bus phenotype also exhibit a ''Skiddy'' (Skd) locomotory mutant phenotype, in which the worm is able to generate a normal sinusoidal wave pattern but its body exhibits extensive slippage on agar and makes little forward progress. The three genes examined in detail in this work have only minor effects on this component of motility; bus-12 and bus-4 mutants exhibit a slight Skd phenotype, while bus-2 mutants move almost normally under normal laboratory conditions.…”
Section: Resultsmentioning
confidence: 76%
“…bus-8 mutations cause cuticle defects that allow multiple drugs to invade the worm cuticle. We chose the bus-8 allele e2698 because it has high cuticle permeability to diverse small molecules and lectins (6), yet the animals are grossly phenotypically normal (7). We confirmed that motor function in the bus-8(e2698) animals is similar to wild type using a standard liquid thrashing assay (Figure S1), and that bus-8(e2698) has increased sensitivity to several different toxic compounds (Figure S2).…”
Section: Resultsmentioning
confidence: 99%